2021
DOI: 10.3390/diagnostics11071184
|View full text |Cite
|
Sign up to set email alerts
|

Acute Zonal Occult Outer Retinopathy (AZOOR) Results from a Clinicopathological Mechanism Different from Choriocapillaritis Diseases: A Multimodal Imaging Analysis

Abstract: Background and aim: AZOOR is a rare disease characterized by loss of zones of outer retinal function, first described by J Donald Gass in 1993. Symptoms include acute onset photopsias and subjective visual field losses. The syndrome is characterized by a normal fundus appearance, scotomas and electroretinographic changes pointing towards outer retinal dysfunction. Evolution, response to immunosuppressive treatment and outcome are difficult to predict. The aim of this small case series was to identify the morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…The overall prognosis is generally favorable since AZOOR is a self-limiting disorder in most cases. Usually, the extent of visual field loss stabilizes after two to six months following the index event [1,9,15]. The follow-up of our patient supports these data, since no disease progression was observed over five years without targeted medical treatment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The overall prognosis is generally favorable since AZOOR is a self-limiting disorder in most cases. Usually, the extent of visual field loss stabilizes after two to six months following the index event [1,9,15]. The follow-up of our patient supports these data, since no disease progression was observed over five years without targeted medical treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Although the clinical appearance of AZOOR varies depending on disease duration and distribution of lesions, there are some typical features including the demarcating line of progression between the involved and uninvolved retina, the trizonal pattern of sequential involvement of the outer retina, retinal pigment epithelium, and choroid, as well as frequent zonal progression [11][12][13][14]. In our patient, the development of symptoms, distribution, and morphology of abnormalities mimicked those in previously reported cases [9,10,15].…”
Section: Discussionsupporting
confidence: 80%
“…All these studies failed to perform ICGA that could have shown choriocapillaris nonperfusion not apparent on OCT-A [ 33 , 66 ]. In contrast, a perfect example of primary outer retinal, photoreceptor disease (photoreceptoritis) is represented by acute zonal occult outer retinopathy (AZOOR) [ 80 , 81 ].…”
Section: Clinicopathology Of Mewdsmentioning
confidence: 99%
“…However, when considering strict diagnostic criteria including, in addition to clinical signs and symptoms, unilaterality, the triad of ICGA, BL-FAF and SD-OCT, in several of these conditions MEWDS can be ruled. For instance, AZOOR which shows similar BL-FAF and SD-OCT signs has preserved choriocapillaris not presenting ICGA hypofluorescent areas [ 81 ]. Of the 13 patients reported as masquerading MEWDS, two conditions, syphilis, in particular ASPPC, and MFC, occurring in five reported patients, cause a real differential diagnostic problem as the clinicopathological mechanism is comparable [ 46 , 72 , 79 ].…”
Section: Overlapping Syndromes and Masquerades Of Mewdsmentioning
confidence: 99%
“…In the convalescent stage of the disease these areas are again filled with ICG. Consequently, MEWDS cannot be a primary photoreceptoritis, which, in contrast, is the case of AZOOR [29]. Multimodal imaging allowed to demonstrate that AZOOR is a true primary disease of the external retina.…”
Section: Mewdsmentioning
confidence: 99%